The Greek influence on Arabic grammar - Yaacob, Solehah@Nik Najah Fadilah (Kamla-Raj Enterprise, 2011)
The purpose of the article is to reexamine the validity of the influence of Greek concept of thinking on the Arabic Language. Is it the case that influences which have been claimed by some intellectuals are concentrated on vocabulary, the linguistic corpus or the grammatical system of Arabic itself?